If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5(x + 1) = 6 + -2(5x + 7) Reorder the terms: 5(1 + x) = 6 + -2(5x + 7) (1 * 5 + x * 5) = 6 + -2(5x + 7) (5 + 5x) = 6 + -2(5x + 7) Reorder the terms: 5 + 5x = 6 + -2(7 + 5x) 5 + 5x = 6 + (7 * -2 + 5x * -2) 5 + 5x = 6 + (-14 + -10x) Combine like terms: 6 + -14 = -8 5 + 5x = -8 + -10x Solving 5 + 5x = -8 + -10x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '10x' to each side of the equation. 5 + 5x + 10x = -8 + -10x + 10x Combine like terms: 5x + 10x = 15x 5 + 15x = -8 + -10x + 10x Combine like terms: -10x + 10x = 0 5 + 15x = -8 + 0 5 + 15x = -8 Add '-5' to each side of the equation. 5 + -5 + 15x = -8 + -5 Combine like terms: 5 + -5 = 0 0 + 15x = -8 + -5 15x = -8 + -5 Combine like terms: -8 + -5 = -13 15x = -13 Divide each side by '15'. x = -0.8666666667 Simplifying x = -0.8666666667
| 3x-14+3x=7+6x-21 | | -2r=-18 | | 8(x+1)=4-2(8x+5) | | 9x=4x+25 | | 0=2x-1 | | 66-5x=9x-4 | | 7x-4+5x+8=160 | | 7(3x+6)=-(x+2) | | (3x-8)(5x+7)-(3x-5)(5x+4)=0 | | 3(q+18)=21-3(q+5) | | 4(3x-2)+=13x+10-12 | | -2.5+a=6.2 | | -12x-3=9 | | 1/4(x+1)=1/10(5-x) | | x^3-60x^2+800x=0 | | (4x+1)-6+(3x-4)=5x | | 3x-8=2x+3 | | -9b+6+7b=-3b+4 | | -19=-13w | | 0=x^2-40x+100 | | 8y-10-6y+7=0 | | 5y-13y=-39-49 | | 2(4-x)=12x-20 | | -6n=6 | | 2x^2+6x+7= | | 56+4y-21=16y-14-5y | | 81q^2-1296= | | 2x+4=x+2 | | 14X+13=-8(-2X+5)-7 | | (y^2)(6y+36)=0 | | x+20+2x=-17-2x-23 | | 10x-6=50x+18 |